WORKING CAPITAL MANAGEMENT AND FIRM'S PERFORMANCE STUDY OF INDIAN MANUFACTURING COMPANIES - Pushpa Negi; Shilpa Sankpal; Anindita Chakraborty; Garima Mathur (Abhigyan, 2010)
The aim of this study is to analyze the effect of working capital management on firm's performance. In accordance with this aim to consider statistically significant relationship between firms Operating Profit Margin and the component of Working Capital Management of Indian Manufacturing companies for the period of 2003 to 2008 has been analyzed under a multiple regression model. The findings of the study indicate that current asset to total asset, total debtors to total asset and inventory days are directly related variables with working capital management, and have significantly negative effects on firm profitability and the other variables included in the regression model (Asset Turnover, Gearing, Current liability to total asset, accounts payable and current ratio) have no statistically significant effect on firms profitability.